CINE Y MITOLOGÍA DE LOS ORÍGENES EN EL NACIONALISMO NORTEAMERICANO: EL ÚLTIMO MOHICANO - RAFAEL MENÉNDEZ FERNÁNDEZ (Fonseca, Journal of Communication, 2023)
Cinema and nationalism show an interesting and ongoing relationship, especially through genres like epic, historical or adventure. We study in this article this relationship from the film "The Last of the Mohicans", directed by Michael Mann in 1992, which presents key elements for understanding the importance of the conformation of the myths about the origins of the American nation.